Fate of Pyrethroids in Freshwater and Marine Environments - Méjanelle, Laurence; Jara Vergara, Bibiana Andrea; Dachs, Jordi (My University, 2020)
As a consequence of their increasing use, pyrethroid insecticides are recognized as a threat for nontarget species and ecosystem health. The present chapter gives a state-of-art overview of individual pyrethroid occurrence in waters and sediments worldwide, together with recent reports of their quantification in the atmospheric gas and aerosol phases. Degradation rates, transport processes, and partitioning of pyrethroids between environmental phases are reviewed. River flow efficiently transports pyrethroids to river mouths and estuaries, while pyrethroid impact on the marine environment remains difficult to appraise due to lack of comprehensive studies. Nevertheless, aquaculture arises as an important but poorly understood environmental burden. Owing to their large organic carbon pool, sediments may act as a sink for pyrethroids and impair nontarget aquatic species. Partitioning potential of pyrethroids is compared to that of other well-known legacy pollutants in the light of their position in the phase space defined by key physicochemical properties (KOW and H′). The transport and partition of pyrethroids away from their source are strongly dependent on their half-life, but their quasi constant emissions in urban and agricultural area may compensate for their degradation, therefore sustaining the occurrence and behavior of some individual pyrethroids as "quasi persistent organic pollutants."
Keywords: air; freshwater; marine; partition; pyrethroids; sediment; transport; water